Stochastic simulation of orbital uncertainty of potentially hazardous asteroids observed in one appearance - Avdyushev, V. A. (Planetary and space science)
The paper discusses some features in stochastic simulation of the orbital uncertainty of potentially hazardous asteroids observed in one appearance (opposition). Due to scant observational information, most of these asteroids have huge orbital uncertainties which can be difficult for stochastic simulation because of the strong nonlinearity of the inverse problem. In the paper we present different stochastic methods for simulation of orbital uncertainty and analyze their efficiency; using an original nonlinearity indicator, investigate the nonlinearity for all potentially hazardous asteroids observed in one opposition; consider the conditions that entail strong nonlinearity as well as the causes of falsely strong nonlinearity.